PENGARUH PEMBERIAN REBUSAN DAUN BINAHONG (Anredera cardifolia (Ten.) Steenis) TERHADAP PENYEMBUHAN LUKA PADA MENCIT (Mus musculus): PENGARUH PEMBERIAN REBUSAN DAUN BINAHONG (Anredera cardifolia (Ten.) Steenis) TERHADAP PENYEMBUHAN LUKA PADA MENCIT (Mus musculus) - Fathita, Afrilla Styva; Primawati, Sri Nopita; Efendi, Ismail (Samota Journal of Biological Sciences, 2025)
This research was conducted to determine the effect of giving a decoction of binahong leaves (Anredera cardifolia (Ten.) Steenis) on wound healing in mice (Mus musculus). This research was conducted from January to May 2024 at the Biology Laboratory, Faculty of Science, Engineering and Applied Sciences, Mandalika Education University. The method used in this research is an experimental method with the RAL technique (Completely Randomized Design). This study used 7 treatments with 4 replications. The data obtained were analyzed using One-way ANOVA, namely SPSS, and if differences were found between treatment combinations. The results of the research were from boiling binahong leaves for different times from 3 minutes, 6 minutes, 9 minutes, 12 minutes and 15 minutes and added positive control and negative control. There were 28 mice (Mus musculus) used divided into 7 treatments. The mice used were 2 month old males weighing 20-25 grams per head. With the aim of knowing the effect of giving a decoction of binahong leaves (Anredera cardifolia (ten.) Steenis) on wound healing in mice (Mus musculus) and showing the results of several data which are classified as significant, namely H4, H5, H6, H8, H9 and H10 due to low values from 0.05, on H4 the sig value. 0.029<0.05, H5 sig value. 0.004<0.05, H6 sig value.0.020<0.05, H8 sig value. 0.002<0.05, H9 sig value. 0.045<0.05, and H10 sig value. 0.005<0.05 is declared significant, while H7 has a sig value. 0.258>0.05 is not significant. Based on these results, it can be concluded that the P4 treatment on day 10 showed the best results for wound healing in mice (Mus musculus).